Exploring novel cocrystals of milrinone: a cardioprotective drug combined with nutraceuticals and an NSAID - Kenguva, Gowtham; Rekha Rout, Smruti; Shaikh, Tabrez R.; Baidya, Debjani; Shelke, Nikita; Sanphui, Palash; Dandela, Rambabu (CrystEngComm, 2024)
Milrinone is a bipyridine phosphodiesterase (PDE) inhibitor of the second generation. It's a PDE-III antagonist that raises cAMP levels to support heart function and acts as a systemic vasodilator in chronic decongested cardiovascular illness. It is categorised as class II in the Biopharmaceutics Classification System (BCS), indicating that it exhibits poor aqueous solubility and high permeability. Three new cocrystals of the cardioprotective drug milrinone (MR) with two nutraceuticals, e.g. sesamol (SES) and resveratrol (RES), and an anti-inflammatory drug, e.g. niflumic acid (NIF), were successfully synthesised using mechanochemical and solution crystallisation techniques. Thermal analysis (DSC and TGA) and diffraction tools (PXRD and SCXRD) were used to obtain structural insights into all the cocrystals. Their crystal structures indicate that the dimeric interactions in MR are preserved in the crystal structures in addition to carboxylic acid/phenol & ctdot;pyridine heterosynthons. Among the three synthesized molecular solids, MR.SES was more soluble than the native drug. The solubility of the cocrystals was correlated with polar surface contacts, the solubility of the coformer and melting points (inversely). We believe that the new MR.SES cocrystal offers a novel approach to enhance the drug's solubility, which may have a positive impact on its synergistic cardioprotective effects.